Serum levels of omentin, chemerin and adipsin in patients with biopsy-proven nonalcoholic fatty liver disease - EREN, FATİH; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (TAYLOR & FRANCIS LTD, 2011)
Objective. The novel adipokines omentin, chemerin, and adipsin are associated with insulin resistance and the components of the metabolic syndrome. We assayed circulating levels of these molecules and examined their association with clinical, biochemical, and histological phenotypes in patients with nonalcoholic fatty liver disease (NAFLD). Material and methods. Serum levels of omentin, chemerin, and adipsin were assayed by enzyme-linked immunosorbent assay in 99 patients with biopsy-proven NAFLD and 75 control subjects. We analyzed associations between adipokines and the characteristics of patients with NAFLD using multivariable linear regression models. Results. Adipsin levels did not differ between patients and controls, whereas both omentin and chemerin levels were significantly higher in patients with biopsy-proven NAFLD than in controls (both p values <0.001). Serum omentin levels were significantly associated with C-reactive protein (r = 0.29, p < 0.01) and the degree of hepatocyte ballooning (r = 0.27, p < 0.01), whereas chemerin showed a modest association with liver fibrosis (r = 0.22, p = 0.04). After stepwise linear regression analysis adjusting for potential confounders, serum omentin levels retained their independent significance as a predictor of hepatocyte ballooning in patients with NAFLD (beta = 1.42; t = 2.79, p < 0.01). Conclusions. Our results suggest that serum omentin levels are raised in patients with NAFLD regardless of potential confounders and represent an independent predictor of hepatocyte ballooning.
Keywords: Adipokines; enzyme-linked immunosorbent assay; liver fibrosis; nonalcoholic fatty liver disease; METABOLIC SYNDROME; ADIPOSE-TISSUE; THERAPEUTIC TARGETS; PLASMA-LEVELS; ADIPOKINES; STEATOHEPATITIS; BIOMARKERS; EXPRESSION; RECEPTOR; OBESITY